1989
DOI: 10.1128/jb.171.12.6423-6429.1989
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary perspectives on multiresistance beta-lactamase transposons

Abstract: A series of intragenic DNA probes, encoding the major part of the transposase resolvase and inverted repeats of transposons Tn3, Tn2l, and Tn25O1, were used in hybridization assays for homologous DNA sequences in 18 transposons studied. The tnpA and tnpR probes detected extensive homology with Tn3-like and Tn21-like elements for 11 transposons. This high degree of homology was confirmed with the 38-and 48-base-pair inverted-repeat oligonucleotide probes of Tn3, Tn2l, and Tn2S01. The Southern-type gel hybridiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…This reflects the preferred insertion of Tn7 into the E. coli chromosome at the specific insertion site attTn7 [26]. Here, as in other surveys, this has resulted in an increasing identification of the dhfr Ia gene as part of the E. coli chromosome [28,50]. The dhfrla gene accounted for 53 % of the identified trimethoprim resistance mechanisms, and 36 % of all trimethoprim resistant isolates.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This reflects the preferred insertion of Tn7 into the E. coli chromosome at the specific insertion site attTn7 [26]. Here, as in other surveys, this has resulted in an increasing identification of the dhfr Ia gene as part of the E. coli chromosome [28,50]. The dhfrla gene accounted for 53 % of the identified trimethoprim resistance mechanisms, and 36 % of all trimethoprim resistant isolates.…”
Section: Discussionmentioning
confidence: 65%
“…The integron system associated with the Tn2l-group of transposons has been responsible for the accumulation of resistance mechanisms to sulphonamides [45], ,3-lactams [50], aminoglycosides [51], heavy metals [52] and disinfectants [25] as well as the insertion of the dhfr genes encoding for the DHFR types lIc, V [23], VII [25], X [32]. Recently the dhfrla has been found in Tn2I inserted as a gene-cassette that has been shown to be associated with Tn7; however, the integrase of Tn7 seems to have undergone a deletion that has rendered it inoperative [29,32].…”
Section: Discussionmentioning
confidence: 99%
“…6). Recently, we also showed that 6 of 12 1-lactamase multiresistance transposons appeared to have evolved from a common Tn2J-like progenitor (24,25). In most cases, agarose gel electrophoresis of BamHI-AvaI-digested transposon DNAs suggested 650-bp BamHI-AvaI and 620-bp AvaI-AvaI fragments of the same sizes as in Tn2l (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…The physical and functional maps of these transposons suggest that they have evolved from a common progenitor by acquisition of DNA coding for various ,B-lactamases and other resistance genes (24,25 Fig. 6, are related in their transposition functions (12,21,25,32,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation